2020
DOI: 10.37611/ib4ol186-100
|View full text |Cite
|
Sign up to set email alerts
|

Proceso De Atencion De Enfermeria a Familia Con Procesos Familiares Disfuncionales

Abstract: Family functionality is that which allows the promotion for the integral development of its members, as well as a favorable state of health, where its members are internally related as a human group. Likewise, it contributes notably to the interpersonal relationships that are generated within each family, when this harmony is broken, it is predisposed to family deterioration and family dysfunction occurs, affecting its members in all its dimensions. The objective of this study is to develop the Nursing Care Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Examining family members' perceptions of communication with nurses, particularly the aspects they consider effective or ineffective, helps to improve the overall understanding of the elements of family-nurse communication (Rojas Torres et al, 2020). Studies have identified effective communication strategies such as speech management and emotional expression.…”
Section: Discussionmentioning
confidence: 99%
“…Examining family members' perceptions of communication with nurses, particularly the aspects they consider effective or ineffective, helps to improve the overall understanding of the elements of family-nurse communication (Rojas Torres et al, 2020). Studies have identified effective communication strategies such as speech management and emotional expression.…”
Section: Discussionmentioning
confidence: 99%